BIMBINGAN ISLAM MELALUI KESENIAN KILININGAN UNTUK PENGUATAN KESADARAN BERAGAMA - Sawitri, Utari; Kusnawan, Aep; Mujib, Abdul (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This research describes the condition of artists' religious awareness as the initial basis for implementing Islamic guidance services in art studios, analyzes the values of Islamic guidance in Kiliningan arts which have the potential to be used as material for Islamic guidance, and analyzes how Islamic guidance is implemented in Kiliningan art studios. This research uses a qualitative approach with a case study method involving observation, interviews and documentation processes. Research shows that the implementation of Islamic guidance services in art studios is carried out using a small group strategy or fi'ah qolilah through a fitrah approach. The methods used are the ngaguar method, the ngalenyepan method, and the ngalarapkeun method.